Impact of a pharmacist-led educational intervention on knowledge, attitude, and practice toward the rational use of antibiotics among healthcare workers in a secondary care hospital in Punjab, Pakistan - Afzal, Shairyar; Khan, Farman Ullah; Aqeel, Muhammad Tahir; Ullah, Matti; Bajwa, Mishal; Akhtar, Masoom; Majid, Muhammad (Frontiers in Pharmacology, 2024)
Introduction: Growing antimicrobial resistance (AMR) and decreasing efficacy of the available antimicrobials have become a significant public health concern. Antimicrobial stewardship program (ASP) ensures the appropriate use of antimicrobials and mitigates resistance prevalence through various interventions. One of the core components of the ASP is to educate healthcare workers. So, this study aims to identify the impact of pharmacist-led educational intervention targeting knowledge, attitude, and practices regarding rational antibiotic use among healthcare professionals in a secondary care hospital of Punjab. Methods: This is a single-center, questionnaire-based, pre-post interventional study conducted over a six-month time period. Data analysis was done using SPSS version 26. Results: Regarding the pre-interventional KAP score of the respondents' 90.3% had a good knowledge score, 81.5% had a positive attitude, and 72.3% of HWs (excluding doctors) had a good practice score. Additionally, 74.6% of the doctors had good practice. After the educational intervention, there was a significant improvement in the knowledge, attitude, and practice of the respondents' healthcare workers (P-value < 0.001). Whereas males have higher knowledge scores than females in the pre-and post-intervention stages (P-value < 0.05), and doctors differ from nurses regarding knowledge scores in both the pre-and postintervention stage. Conclusion: Considering educational programs as a backbone of ASP, it is imperative to sustain efforts in ongoing educational programs of the HWs to foster high awareness and adherence to ASP among HWs.